Management of the Work Environment to Reduce Blood Lead (BLL) Levels in the Assay Laboratory - Susanto, Arif; Indra Komara, Yopi; Mohamad Khaliwa, Agra; Sarah Yuliasari, Fanny; Karyono Putro, Edi (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
Assay Laboratory in PT Freeport Indonesia's Concentrating Division, especially for conducting fire assay. Litharge (lead oxide) is a reagent used to test mineral levels; the content of precious metals is called Au. Although lead exposure is low, prolonged exposure to lead could accumulate in the human system, resulting in poisoning or toxicity. This study aimed to determine the effect of work environment management in assay laboratories on reducing blood lead levels during fire assay analysis. This research is a quantitative cohort study. The sampling technique used is purposive sampling. Data analysis techniques are used in different tests. Data collection was conducted using laboratory tests to take blood samples once a year regularly for every worker working in the assay laboratory. Based on the results of the different tests, a T value of 5,638 was obtained with a Sig value of 0.011 (α˂5%), so it can be concluded that there was a decrease in blood Pb levels in workers before and after managing the work environment. Recommended exposure standards are floor exposure values for laboratories (other than fire test laboratories) not to exceed 2.2 mg/m2 (200 μg/ft2) and surface in dining areas not to exceed 0.43 mg/m2 (40 μg/ft2). Improving working environment conditions by procuring a laundry system and lockers, procuring more than one laboratory coat, procuring sinks in every corner of the laboratory, and having special soap for washing hands has proven to be able to reduce Pb exposure rates in assay laboratories from 2019 to 2022.